2010
DOI: 10.1007/s11664-010-1321-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of IR-Laser-Irradiated HgCdTe

Abstract: We study laser-induced nonequilibrium processes in intrinsic Hg 1Àx Cd x Te with alloy fractions x = 0.2 and x = 0.28. Excitations of nanosecond to microsecond duration with an intensity of 2 MW/cm 2 to 20 MW/cm 2 at four selected wavelengths from 3.8 lm to 10.6 lm are considered. Recent publications indicate significantly longer Auger lifetimes than those previously found in the literature. We discuss the consequences of this and introduce improved descriptions of Auger recombination, impact ionization, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Energy transfer due to long, high fluence laser pulses on the other hand, often increases the overall lattice temperature, but makes possible the investigation of many additional physical effects. In particular, if the photon energy of the incident radiation just exceeds the band gap, absorption can be highly non-linear and depend strongly on wavelength, radiation intensity, carrier temperatures, and lattice temperatures (Storebo et al, 2010). Laser energy pathways between the different carrier ensembles are illustrated in Fig.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy transfer due to long, high fluence laser pulses on the other hand, often increases the overall lattice temperature, but makes possible the investigation of many additional physical effects. In particular, if the photon energy of the incident radiation just exceeds the band gap, absorption can be highly non-linear and depend strongly on wavelength, radiation intensity, carrier temperatures, and lattice temperatures (Storebo et al, 2010). Laser energy pathways between the different carrier ensembles are illustrated in Fig.…”
Section: Generalmentioning
confidence: 99%
“…Although the total number of carriers generated in the conduction band can be comparable to that of a short pulse experiment, the majority of the carriers are well thermalized at temperatures which lie close to the overall lattice temperature. Nevertheless, differences between carrier and lattice temperature smaller than 100 K can have a major impact on processes occurring near the band gap, according to (Storebo et al, 2010). For example, it was found that a slightly elevated carrier temperature can strongly reduce the Pauli-induced saturation or "bleaching" of one-photon absorption across the band gap, or affect other long-timescale parameters, like carrier lifetimes and impact ionization rates.…”
Section: Long Pulse Regimementioning
confidence: 99%